An investigation of the use of the Kinect system as a measure of dynamic balance and forward reach in the elderly. (April 2018) - Hsiao, Ming-Yen; Li, Chia-Ming; Lu, I-Shu; Lin, Yu-Hung; Wang, Tyng-Guey; Han, Der-Sheng
Objective: To investigate the reliability and correlations of Kinect-derived valuables of forward reach distance and velocity with the traditional functional reach distance, scores on posturography, and other measures of physical fitness. Design: Observational study. Setting: Community hospital. Subjects: Individuals >65 years who attended a geriatric health examination were enrolled. Main measures: The Kinect system was used to record the reach distance and velocity of the forward reach test. Center of pressure displacement was measured by posturography. Physical fitness performance was assessed using the 2-Minute Step Test, the 30-Second Chair Stand Test, the Sit-and-Reach Test, grip strength, and walking speed. Results: A total of 442 individuals were enrolled (mean age: 73.3 ± 5.2 years). Forward reach tracking using the Kinect system showed good repeatability and correlated with traditional functional reach ( r  = 0.719, P  < 0.001); the reaching velocity correlated with scores on posturography ( r  = −0.257, P  = 0.047). Reach distances were significantly decreased in the older group (≥75 years) than in the younger group (<75 years) ( P  < 0.001). Conclusion: The Kinect system provides a simple, reliable, and age-sensitive assessment of balance in older adults. The valuables correlate with the traditional functional reach, scores on posturography, and physical fitness performance. It provides alternative representation of both static and dynamic balance function.